Signaling cross-talk between TGF-β/BMP and other pathways - Guo, Xing (2009)
Transforming growth factor-beta (TGF-β)/bone morphogenic protein (BMP) signaling is involved in the vast majority of cellular processes and is fundamentally important during the entire life of all metazoans. Deregulation of TGF-β/BMP activity almost invariably leads to developmental defects and/or diseases, including cancer. The proper functioning of the TGF-β/BMP pathway depends on its constitutive and extensive communication with other signaling pathways, leading to synergistic or antagonistic effects and eventually desirable biological outcomes. The nature of such signaling cross-talk is overwhelmingly complex and highly context-dependent. Here we review the different modes of cross-talk between TGF-β/BMP and the signaling pathways of Mitogen-activated protein kinase, phosphatidylinositol-3 kinase/Akt, Wnt, Hedgehog, Notch, and the interleukin/interferon-gamma/tumor necrosis factor-alpha cytokines, with an emphasis on the underlying molecular mechanisms.